2019
DOI: 10.7150/thno.28892
|View full text |Cite
|
Sign up to set email alerts
|

Imaging fibrosis in inflammatory diseases: targeting the exposed extracellular matrix

Abstract: In a variety of diseases, from benign to life-threatening ones, inflammation plays a major role. Monitoring the intensity and extent of a multifaceted inflammatory process has become a cornerstone in diagnostics and therapy monitoring. However, the current tools lack the ability to provide insight into one of its most crucial aspects, namely, the alteration of the extracellular matrix (ECM). Using a radiolabeled platelet glycoprotein VI-based ECM-targeting fusion protein (GPVI-Fc), we investigated how binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…to image nascent exposure of extracellular matrix during tissue damage, and synthesis of new fibrous tissue in GPI-serum induced experimental arthritis 137 . These approaches constitute the first steps towards detailed molecular analysis of the synovial matrix in real time in vivo.…”
Section: Ra Diagnosis: the Truth Is In The Tissuementioning
confidence: 99%
“…to image nascent exposure of extracellular matrix during tissue damage, and synthesis of new fibrous tissue in GPI-serum induced experimental arthritis 137 . These approaches constitute the first steps towards detailed molecular analysis of the synovial matrix in real time in vivo.…”
Section: Ra Diagnosis: the Truth Is In The Tissuementioning
confidence: 99%
“…In the inflammatory state, the activation of platelets via GPVI signaling has been reported to induce formation of platelet-derived microparticles in the bloodsuggesting a key role for GPVI signaling in the amplification of inflammation. Aligned with evidence that platelet microparticles are known to include transcription factors (e.g., PPARG) and cytokines and chemokines (e.g., IL1), and are hypothesized to function in interactions with other cells (50)(51)(52)(53), our multiomics study reports that key VAT signals from molecular pathways upregulated in patients with high PTGS2 tumor expression involve interacting pathways associated with fibrosis, including GPVI signaling, dendritic cell maturation, and inflammation in patients with colorectal cancer. Our findings were substantiated via independent serum-based inflammatory biomarker profiling, as the elevated expression of SAA2 and enrichment of IL6 signaling were also associated with high tumor PTGS2 expression.…”
Section: Discussionmentioning
confidence: 66%
“…Fibrosis has been demonstrated in several tissues from RA patients and rodent studies. For example, increased fibrous tissue deposition was demonstrated in the joint of RA rodents 6 days post induction with fluorescent visualization of collagen III and fibrinogen [90]. Similarly, research from our group has demonstrated a significant increase in collagen accumulation within the vastus lateralis, soleus and gastrocnemius muscles in CIA rodents compared to that of control rodents [38], as well as impaired molecular remodelling with fibrotic deposition and impaired cardiomyofibre contractile function [91].…”
Section: Fibroblasts and The Extracellular Matrix (Ecm)mentioning
confidence: 61%